Optimal duration of dual antiplatelet therapy after percutaneous coronary intervention with drug eluting stents: meta-analysis of randomised controlled trials - Navarese, Eliano Pio (BMJ, 2015)
Objective To assess the benefits and risks of short term (<12 months) or extended (>12 months) dual antiplatelet therapy (DAPT) versus standard 12 month therapy, following percutaneous coronary intervention with drug eluting stents. Design Meta-analysis of randomised controlled trials. Data sources PubMed, Embase, Cumulative Index to Nursing and Allied Health Literature, Scopus, Web of Science, Cochrane Library, and major congress proceedings, searched from 1 January 2002 to 16 February 2015. Review methods Trials comparing short term (<12 months) or extended (>12 months) DAPT regimens with standard 12 month duration of therapy. Primary outcomes were cardiovascular mortality, myocardial infarction, stent thrombosis, major bleeding, and all cause mortality. Results 10 randomised controlled trials (n=32 287) were included. Compared to 12 month DAPT, a short term course of therapy was associated with a significant reduction in major bleeding (odds ratio 0.58 (95% confidence interval 0.36 to 0.92); P=0.02) with no significant differences in ischaemic or thrombotic outcomes. Extended versus 12 month DAPT yielded a significant reduction in the odds of myocardial infarction (0.53 (0.42 to 0.66); P<0.001) and stent thrombosis (0.33 (0.21 to 0.51); P<0.001), but more major bleeding (1.62 (1.26 to 2.09); P<0.001). All cause but not cardiovascular death was also significantly increased (1.30 (1.02 to 1.66); P=0.03). Conclusions Compared with a standard 12 month duration, short term DAPT (<12 months) after drug eluting stent implementation yields reduced bleeding with no apparent increase in ischaemic complications, and could be considered for most patients. In selected patients with low bleeding risk and very high ischaemic risk, extended DAPT (>12 months) could be considered. The increase in all cause but not cardiovascular death with extended DAPT requires further investigation.